Does Music Training Improve Emotion Recognition Abilities? A Critical Review. (July 2021) - Martins, Marta; Pinheiro, Ana P.; Lima, César F.
There is widespread interest in the possibility that music training enhances nonmusical abilities. This possibility has been examined primarily for speech perception and domain-general abilities such as IQ. Although social and emotional processes are central to many musical activities, transfer from music training to socioemotional skills remains underexplored. Here we synthesize results from studies examining associations between music training and emotion recognition in voices and faces. Enhancements are typically observed for vocal emotions but not for faces, although most evidence is cross-sectional. These findings are discussed considering the design features of the studies. Future research could explore further the neurocognitive mechanisms underlying musician-related differences in emotion recognition, the role of predispositions, and the implications for broader aspects of socioemotional functioning.